The length of the crystalline style of Perna viridis in relation to shell length, shell width and shell height : data for future reference. - Yap, Chee Kong; Edward Thomas, Franklin Berandah; Tan, Soon Guan (Universiti Malaysia Terengganu (UMT), 2010)
The crystalline style (CS) is a gelatinous rod-like body that contains starch-digesting enzymes in the hemolymph of the bivalves. The lengths of the CS, shell lengths, shell widths and shell heights of the green-lipped mussel Perna viridis, collected from seven sampling sites in southern coastal waters of Peninsular Malaysia, were measured. The lengths of CS in relation to shell length, shell width and shell height were 72-73%, 211-218% and 154-157%, respectively. The correlation analysis indicated that the length of CS is positively and significantly (P< 0.001) correlated to the shell length (R= 0.81), shell width (R= 0.82) and shell height (R= 0.64). The percentages of the CS length to the shell parameters could be potentially used to identify the different mussel species since different mussel species have a specific CS length to the shell length. The present findings can serve as an important reference for comparative purpose with other bivalve species.